9 - The Making of the ‘Informal State’ in Uganda - khisa, Moses (Africa Development, 2021)
This article analyses the evolution, reproduction, and sustenance of what I refer to as the ‘informal state’ in Uganda – a distinct mode of organising and broadcasting power that simultaneously centralises and fragments the state system. The ‘informal state’ is manifest in the construction of structures parallel to the legal and constitutional ones. This article departs from other studies of stateness in Africa that accent colonial legacies, illicit economic activities, and social conflict in accounting for the so called ‘African state’ that supposedly fails to approximate to the model (modern) state. Instead I argue that Uganda’s ‘informal state’ is a consequence of three key factors: the country’s post- independence experience with wide-spread insecurity and political instability in the 1970s and 1980s, the belief in militarism as an ideology by the new (post- 1986) group of rulers along with the imperatives of retention of political power, and foreign-aid flows as reward for embracing neoliberal economic reforms. The article also shows that the ‘informal state’ system reproduces its survival and legitimates its rule through maintaining aspects of legal-rational state structures, ceding power to varied constituencies as well as expanding the patronage network through the creation of numerous agencies.